Peers' Race in Adolescence and Voting Behavior - Maria Polipciuc; Frank Cörvers; Raymond Montizaan (Institute of Labor Economics (IZA), 2021)
Using a representative longitudinal survey of U.S. teenagers, we investigate how peer racial composition in high school affects individual turnout of young adults. We exploit across-cohort, within-school differences in peer racial composition. One within-school standard deviation increase in the racial diversity index leads to a 2.2 percent increase in the probability of being registered to vote seven years later and to a 2.6 percent higher probability of voting six years later. These effects are likely due to positive interracial contact when socialization has long-lasting effects: higher racial diversity in school is linked to more interracial friendships in school and later on.
Keywords: D72; I24; J15; 330; voting behavior; school-cohort racial diversity; peers